Integral group ring of Suzuki sporadic simple group (2008)
Using the Luthar–Passi method, we investigate the classical Zassenhaus conjecture for the normalized unit group of the integral group ring of the Suzuki sporadic simple group Suz. As a consequence, for this group we confirm the Kimmerle’s conjecture on prime graphs.